A study of academic cooperation networks in the research function of Literature studies at the Universidad Nacional de la Patagonia Austral (1996-2016) - Forchino, María Verónica; Gasel, Alejandro Fabian (AWARI, 2023)
By utilizing the social network analysis methodology, based on publicly available data from research project reports, we observe the dynamics of collaboration, invisible colleges, and the emergence and consolidation of research groups. Within this framework, this study aims to investigate the dynamics of academic collaboration at the Universidad Nacional de la Patagonia Austral (UNPA) through the analysis of participation networks in scientific events among research groups in the field of Literature (including literary, linguistic, and semiotic studies) during the period from 1996 to 2016. The findings uncovered have the potential to provide insights into the institutionalization dynamics of research in the field of literature. Leveraging both social network and affiliation network analyses, this study reveals patterns that shed light on various strategies for consolidating research efforts within specific realms of literary exploration. Through participation in scientific events, researchers establish invisible intellectual communities that contribute to forming closely connected networks that gradually define their spaces and spheres of influence. This case study is a foundational effort, emphasizing the importance of complementing socio-historical studies of academic institutionalization with intricate analyses of intellectual networks. This comprehensive approach enriches understanding of the collective construction dynamics inherent within the scientific field.